HERPES ASSOCIATED-ERYTHEMA MULTIFORME (HAEM) IN YOUNG ADULT - Lukman Hakim Hidayat (Faculty of Dentistry, Universitas Islam Sultan Agung, 2018)
Background: Erythema multiforme is an acute and a self-limiting mucocutaneoushypersensitivity reaction triggered by infections and medications. The mostcommon predisposing factors for erythema multiforme is infection with herpessimplex virus. Herpes associated erythema multiforme (HAEM) is an acuteexudative dermatic and mucosal disease caused by the infecting herpes simplexvirus. Most common ages is in childhood.Case and management: We report a case of recurrent herpes-associatederythema multiforme in a 23-year-old female patient, with crustae lesion in thelips and in pain. The patient had history of HSV infection. The patient had afever and prodromal before the lesion emerge. And the cutaneous lesion wasmistaken with the pimpleacne.Conclusions: Although the etiology of EM is still often unknown, infections withherpes simplex virus have been implicated as common predisposing a possibleprecipitating factor. This case illustrates the association of the occurrence of EMwith a herpes simplex virus (HSV) infection and how to managed the lesion